Prenatal dietary supplements influence the infant airway microbiota in a randomized factorial clinical trial - Mathis H. Hjelmsø (Nature Portfolio, 2020)
Here, the authors present the results of a mother–child cohort randomized clinical trial of n-3 LCPUFA and vitamin D maternal supplementation, finding an association between supplement-induced microbiota changes in infant airways at age 1-month but not the infant fecal or maternal vaginal microbiome.